Role of Alexithymia in the Association Between Childhood Abuse and Risk Perception for Sexual Victimization in College Women - Kiefer, Reina (Journal of interpersonal violence, 2024)
Sexual victimization is prevalent among college women with a history of childhood abuse (CA), which some research suggests is linked to impaired risk perception for sexual victimization or difficulties identifying and responding to unwanted sexual advances. Alexithymia is one construct yet to be examined in the association between CA and risk perception for sexual victimization. The purpose of this study was to elucidate the associations between CA, alexithymia, and risk perception for sexual victimization in a sample of college women with a history of CA. Participants included 294 undergraduate women with a history of childhood emotional, physical, and/or sexual abuse (Mage = 20.6, 80.6% White). An a priori path analysis was conducted to examine whether alexithymia indirectly explains the association between CA and risk perception for sexual victimization (i.e., comprising two related constructs, including threat detection and behavioral response to threat). Supplementary analyses were conducted post hoc to examine potential differences across CA subtypes (emotional, physical, and sexual). Alexithymia indirectly explained the relationship between CA and threat detection, and behavioral response to threat. However, indirect effects were negative, suggesting that undergraduate women with more severe CA and alexithymia identify sexual assault threat cues and intentions to “leave” a hypothetical sexual assault scenario sooner rather than later. The same pattern of results was observed for emotional and physical (but not sexual) CA when examining their indirect effects on threat detection, and for emotional CA when examining behavioral response to threat. Findings contribute to the literature on sexual victimization by clarifying the role of alexithymia in risk perception for sexual victimization. Results also highlight the potential utility of increasing emotional literacy among college women with a history of CA (and especially emotional abuse) to facilitate adaptive responding to unwanted sexual advances.